Strategi Komunikasi Politik Eko Muji Suharto dari PDI Perjuangan dalam Memenangkan Kursi Anggota DPRD Sragen pada Pemilu Legislatif Tahun 2019: Strategi Komunikasi Politik Eko Muji Suharto dari PDI Perjuangan dalam Memenangkan Kursi Anggota DPRD Sragen pada Pemilu Legislatif Tahun 2019 - Saefudin, Ade Arif; Sarjono, Herning Suryo; Kusumo Aji, Haryo (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
A political communication strategy is a communication plan and guide, so it must show theoperational method that functions as a direction to achieve the goal. Eko has run three times as amember of the Sragen DPRD, namely in 2009, 2014 and 2019. However, in 2014 he failed, sohe evaluated his communication strategy and won again in 2019. This research aims to describehow Eko Muji Suharto's political communication strategy from PDI Perjuangan in winningthe seat of Sragen DPRD member. The type of data used in this research is qualitative data. Thedata sources used are primary data sources and secondary data. This research uses the interviewmethod conducted on Eko Muji Suharto, 2 Jatitengah Village communities, and 2 PDIPerjuangan cadres. The data analysis techniques used are data collection, data reduction, datapresentation and verification carried out during the research. The results of the study are firstseen from the communicator aspect, he meets the requirements to be a good politicalcommunicator as measured by his capacity, competence, personality, and education. Measuredfrom the aspect of the message, namely the political message conveyed contains the vision andmission and is in accordance with what is the unrest and needs of the community. Measuredfrom the aspect of the recipient of Eko's political message is also targeted precisely at all peoplewho already have the right to vote. So that in the aspect of the effects arising from thecommunication strategy carried out by Eko it worked well, namely in the form of support fromthe audience.Keywords: PDI Perjuangan, Winning seats, DPRD